Verification of Total Plate Count Testing Method on Dairy Goat Milk Referring to SNI 2897: 2008 - Suryaningsih, Putu ayu; Suyasa, Ida Bagus Oka (Jurnal Skala Husada : The Journal of Health, 2025)
Background: A method must be verified and validated because each laboratory has varying conditions. This diversity can occur due to differences in facilities, personnel competence, equipment and chemicals used. In addition, accredited testing laboratories have an obligation to carry out method validation and verification processes before implementing the method. Objective: In this study, the ALT testing method for dairy goat milk was verified using accuracy and precision test parameters from samples with low, medium, high and uncontaminated concentrations. Method: This research uses descriptive research, namely describing the results of verification of the ALT testing method on fresh goat's milk which refers to SNI 2897:2008. Results: The SNI 2897:2008 ALT testing method on dairy goat milk for all microbial concentrations can be applied at the Denpasar Ministry of Health Health Polytechnic Integrated Laboratory because the RSD and Percent Recovery values do not exceed the limits set in SNI 2897:2008. Conclusion: The Total Plate Number testing method according to SNI 2897:2008 with a dairy goat's milk matrix can be applied as a testing method at the integrated laboratory of the Health Polytechnic of the Ministry of Health, Denpasar.